2021
DOI: 10.1161/atvbaha.121.315928
|View full text |Cite
|
Sign up to set email alerts
|

Anti-dsDNA Antibodies Increase the Cardiovascular Risk in Systemic Lupus Erythematosus Promoting a Distinctive Immune and Vascular Activation

Abstract: Objective: Systemic lupus erythematosus (SLE) is associated to boosted atherosclerosis development and a higher cardiovascular disease risk. This study aimed to delineate the role of anti-double stranded DNA (anti-dsDNA) antibodies on the molecular profile and the activity of immune and vascular cells, as well as on their enhanced cardiovascular risk. Approach and Results: Eighty SLE patients were included. Extensive clinical/analytical evaluation was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 34 publications
2
24
0
Order By: Relevance
“…Certainly, antibody production predominantly took place in the plasma, pointing to an ingress of peripherally activated B cells/antibodies. In line with recent findings identifying new onset autoantibodies in patients with COVID-19 (4), our identification of elevated anti-dsDNA IgG, which are associated with cardiovascular symptoms in systemic lupus (23), may provide a potential pathophysiological rationale for cardiovascular risk factors in severe COVID-19 (24). Indeed, two out of four class lll patients with vascular complications had increased levels of anti-dsDNA IgG in the CSF.…”
Section: Discussionsupporting
confidence: 85%
“…Certainly, antibody production predominantly took place in the plasma, pointing to an ingress of peripherally activated B cells/antibodies. In line with recent findings identifying new onset autoantibodies in patients with COVID-19 (4), our identification of elevated anti-dsDNA IgG, which are associated with cardiovascular symptoms in systemic lupus (23), may provide a potential pathophysiological rationale for cardiovascular risk factors in severe COVID-19 (24). Indeed, two out of four class lll patients with vascular complications had increased levels of anti-dsDNA IgG in the CSF.…”
Section: Discussionsupporting
confidence: 85%
“…Anti-dsDNA antibodies are considered as a critical marker for the diagnosis and classification of SLE. Moreover, the fluctuating titers of these antibodies reflect the activity of disease of many patients; a rising titer could be predictive of disease relapse [25]. According to previous studies, higher levels of anti-dsDNA antibodies were detected in patients with active SLE [26].Another previous study, in line with ours, showed that anti-dsDNA antibodies levels appear to remain similar in sera of SLE patients after being infected with T. gondii [27].…”
Section: Discussionsupporting
confidence: 81%
“…In addition, the parameters related to increased cardiovascular risk were associated with the presence and titer of anti-dsDNA antibodies, and the relationship was independent of the other cardiovascular risk factors ( Patiño-Trives et al, 2021 ). Certainly, glucocorticoid exposure may also play an important role in CVDs, for example, the high-dose of prednisolone promote carotid intima-media thickness progression in SLE ( Ajeganova et al, 2020 ; Lengton et al, 2021 ).…”
Section: Discussionmentioning
confidence: 98%